The impact of Quaternary sea level changes on the evolution of the Amazonian lowland - Irion, George F.; Müller, Jens; Morais, Jáder Onofre de; Keim, Gertrud; Mello, Jose Nunes de; Junk, Wolfgang Johannes (Hydrological Processes, 2009)
Coring and acoustic surveying (3.5 kHz) in both rivers and lakes in Central Amazonia provide additional insights into the Late Quaternary hydrological and sedimentological development of the Amazon River and its tributaries. Erosion and accumulation phases were found to be linked to Quaternary sea level changes. The low sea level phase during the last glacial maximum caused deep incision of the Amazon River and erosion in major tributaries such as the Rio Negro, 1500 km upstream from the Amazon mouth. A 3.5-kHz profiling suggests a lowering of the water level by at least 30 m at Manaus. During that phase, the slope of the Amazon valley must have increased, resulting in an increase in bed load transport capacity. The subsequent sea level rise caused a backwater effect far upstream, with silting up of the Amazon valley and the tributary inflows. Former river systems changed into Ria lakes. The floodplains of the Amazon River, the várzea, were formed approximately 5000 years ago when the sea level approached its present-day level. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Erosion; Lakes; Sea Level; Sediment Transport; Sediments; Water Levels; Amazonia; Backwater Effects; Bed-load Transport; Last Glacial Maximum; Quaternary (late); Rivers And Lakes; Sealevel Change; Rivers; Erosion; Floodplain; Landform Evolution; Lowland Environment; Quaternary; Sealevel Change; Sediment Transport; Tributary; Amazon River; Amazonia; South America